Utilization of dolomite with different percentage of fly ash replacement as alkali activated materials for bricks application - Emy Aizat Azimi (School of Materials Engineering, 2019)
This study is focusing on the utilization of waste material from the dolomite industry, which is dolomite as major raw material for geopolymer. The fly ash was also used as a modification and replacement in the dolomite geopolymer. The characterization of dolomite and fly ash is analysed using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscope (SEM). In order to develop dolomite based geopolymer, various mix designs were carried out and the optimum mix design is defined by geopolymer samples to contribute to high compressive strength. The parameter included in the mix design of the geopolymer paste is NaOH concentration, solid/liquid ratio, and sodium silicate/sodium hydroxide (NaOH) ratio. The characterization of D/FA based geopolymer was also evaluated using XRD, FTIR, XRF, and SEM. In order to produce bricks using dolomite/fly ash materials, various ratios of dolomite and fly ash amount were used. The production of D/FA geopolymer bricks is carried out to study the strength properties of this application. The strength of the bricks were determined by compressive strength while the water absorption of the bricks was also investigated by using water up to seven days. The temperature resistant properties of D/FA geopolymer evaluated using temperature exposure in furnace.